The proceedings upon the bill of divorce between His Grace the Duke of Norfolke and the Lady Mary Mordant : viz, I, the Journal of the House of Lords . - Norfolk, Henry Howard, Duke of, 1655-1701 (British trials, 1660-1900, 1700)
Lady Mordant, Duchess of Norfolk, was accused by her husband the Duke of Norfolk, of adultery with John Germain; later she became Lady Germain.